2014
DOI: 10.1007/s10528-014-9644-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Diversity of Honey Bees (Apis mellifera) from Unmanaged Colonies and Swarms in the United States

Abstract: To study the genetic diversity of honey bees (Apis mellifera L.) from unmanaged colonies in the United States, we sequenced a portion of the mitochondrial DNA COI-COII region. From the 530 to 1,230 bp amplicon, we observed 23 haplotypes from 247 samples collected from 12 states, representing three of the four A. mellifera lineages known to have been imported into the United States (C, M, and O). Six of the 13 C lineage haplotypes were not found in previous queen breeder studies in the United States. The O line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 34 publications
1
41
4
Order By: Relevance
“…The C1 haplotype was found from 52 % (123 of 235, Table II) of the samples. Magnus et al (2011) found the C1 haplotype to be the most common haplotype in the continental United States, while Delaney et al (2009) found haplotype C1 to be the most common in Southern United States, and the second most common in Western United States. Four of the C lineage haplotypes (C1, C2, C11, and C19) have been observed in samples from queen breeders in the continental United States (Delaney et al 2009;Magnus et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The C1 haplotype was found from 52 % (123 of 235, Table II) of the samples. Magnus et al (2011) found the C1 haplotype to be the most common haplotype in the continental United States, while Delaney et al (2009) found haplotype C1 to be the most common in Southern United States, and the second most common in Western United States. Four of the C lineage haplotypes (C1, C2, C11, and C19) have been observed in samples from queen breeders in the continental United States (Delaney et al 2009;Magnus et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This lineage has became preferred by most beekeepers and is bred by nearly all commercial beekeepers in the continental United States (Sheppard 1988(Sheppard , 1989aSchiff and Sheppard 1996). Although there are five mitochondrial DNA (mtDNA) lineages worldwide, managed honey bees in the USA are dominated by the C lineage (Delaney et al 2009;Magnus et al 2011). with the M lineage and O lineages comprising 7 and 9 % of unmanaged honey bees (excluding A lineage) in the United States (Magnus et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods based on the analysis of COI-COII sequences in mitochondrial DNA (mtDNA) have been widely used in the determination of honeybee lineages (Magnus, Tripodi, & Szalanski, 2011;Meixner et al, 2013;Coroian et al, 2014). Six evolutionary lineages (A, C, M, O, Y, and Z) have been found in A. mellifera according to morphometric or molecular studies (Ruttner, 1988;Franck et al, 2001;Alburaki et al, 2013).…”
mentioning
confidence: 99%